Bellezza del Manifesto di Ventotene (Materiali di Estetica. Terza serie, 2020)
In March 2019, a series of Aesthetic Conversations on "European Souls" was held at the Fondazione Corrente in Milan. This article is my report to one of the conversations dedicated to the birth of the idea of ​​a free and united Europe, in a small island of confinement, during one of the darkest and most dramatic pages in human history.
Keywords: Europe; Ventotene; Freedom; Union